INFORMATION TECHNOLOGY AS A MEANS TO CAPTURE THE STUDENTS OF THE COURSE "METHODS OF "MATHEMATICS" EDUCATIONAL TEACHING FIELD" - Skvortsova, С.О.; Garan, М.С. (Journal of Information Technologies in Education (ITE), 2015)
The paper presents an analysis of the concepts of "information technology", "Information Technologies in Education", "Information technology education", "computer technology", "New Information Technologies", "New Information Technologies in Education". Found that the most common concept in this list is the concept of "information technology" as a set of methods and technical means for collecting, processing, storing, processing, transmission and presentation of data. Slightly narrower in this context, the concept of "new information technologies," which mandates the involvement of computer and other technical means to work with data. The emphasis on the learning process of information technology requires detailed terms "Information Technologies in Education" and "New Information Technologies in Education", which are defined as involvement of information technology and accordingly, including the technical means to create new perceptions and knowledge transfer, evaluation studies and all-round development of the individual in the educational process. Along with these terms also used such as "information technology training," which denotes a set of training and educational materials, and technical tools for educational purposes, as well as the system of scientific knowledge about their role and place in the educational process. Meanwhile, the term "information technology" encompasses all these concepts, so in a broad sense can be used to denote any signified concepts. As an extension of the term "information technology", the term information and communication technologies (ICT), and "information technology education", understood as educational technology using special methods, software and hardware to work with information and "ICT training "- as IT training focused on the use of computer communications networks for solving instructional problems or their fragments. Taking into account tasks, such as creating methodical maintenance of discipline "Methods of teaching educational sector" Mathematics "" using computers, the authors use the term "information technology", follow the definition of information technologies M. Zhaldak, IT training Zakharova I. and see their possible implementation in class presentations through the use of lectures; at workshops – by presentations prepared by the teacher and presentations prepared by the students, and through the use of computer control tests; during independent work possible use of teaching aids in electronic media and educational computer tests.